The Role of School Administrations and Educational Curricula in Promoting the Intellectual Security of Students - Mariam Abdullah Ahmad; Amnah Hassan Dammas (Intelektual Pustaka Media Utama, 2018)
This study aims at identifying the role played by school administrators' and curricula in promoting intellectual security of students. To achieve this purpose, the researchers adopted the descriptive approach. Data were gathered and analyzed by using a questionnaire that determines the role of school administrations and curricula in the promotion of intellectual security. The questionnaire includes two sections: first; the respondents' profile information, second; sixteen 5-point Likert-type questions. The study sample consisted of 27 male and 14 male. The data obtained from the questionnaire show that school administrators', extracurricular activities, and curricula had a statistically significant effect on promoting intellectual security of students respectively. For this research study, results, along with practical implications and recommended future research directions were discussed.